The Safety of Radiotherapy in the Treatment of Primary Cutaneous B-Cell Lymphoma: A Multidisciplinary Systematic Review - Di Stefani, Alessandro; Tagliaferri, Luca; Lancellotta, Valentina; Fionda, Bruno; Fossati, Barbara; Balducci, Mario; Federico, Francesco; Hohaus, Stefan; De Simone, Clara; Gambacorta, Maria Antonietta; Peris, Ketty (Frontiers in Oncology, 2020)
Primary cutaneous B-cell lymphomas (PCBCL) are rare types of extranodal non-Hodgkin's lymphoma. The choice of treatment usually depends on the variant of PCBCL, number, size, and location of the lesions, involved body surface area as well as patient's age and health condition. The efficacy of radiotherapy (RT) in the treatment of PCBCL has been widely reported conversely, data about the acute and late skin toxicity, patient's treatment satisfaction and quality of life are scarce. A systematic search using PubMed, Scopus, and Cochrane library was performed to identify full original articles analyzing the safety of RT in patients with PCBCL with the primary outcome to assess the acute and late skin toxicity. Secondary outcomes were complete remission, disease free survival, and overall survival. The literature search resulted in 276 articles including eight studies assessing the safety of RT for the treatment of PCBCL. Most patients (median 73%, range 11.9–99.9%) were recorded as having acute skin toxicity of grade 1–2, while acute grade 3–4 toxicity occurred in a median of 8% (range 4–23%) of patients. A median of 20% (range 4–54%) of patients had late skin toxicity of grade 1–2. No late grade 3–4 toxicity was reported. Only one study evaluated patient's satisfaction showing that the 97% of patients were satisfied with radiation therapy. This systematic review confirms the safety of RT in the treatment of PCBCL. Patients with a PCBCL should be managed in highly specialized centers in the context of a multidisciplinary team including dermatologist, hematologist, pathologist, and radiation oncologist.